Corporate governance and organizational commitment: The mediating role of organizational culture - Najm Abood Najm; Abdul Azez B. Alnidawy; Abdul Sattar H. Yousif (European Journal of Government and Economics (EJGE), 2022)
This study seeks to determine the impact of corporate governance dimensions (compliance with the corporate governance code, top management, control environment, transparency and disclosure, rights of shareholders and stakeholders) on the three main types of organizational commitment, (affective, continuance and normative). It also aims at examining the impact of organizational culture, as an intermediate variable, on the relationship between the two above mentioned variables. The sample of this study comprised 152 respondents working at five types of Jordanian companies. The results of the study have confirmed the positive effect of the three corporate governance dimensions (compliance with the corporate governance code, top management, and control environment) on three types of organizational commitment (affective, continuance, and normative). The results also confirmed that there is no significant effect of t transparency and disclosure and the rights of shareholders and stakeholders on affective and normative commitment.
Keywords: 330; corporate governance; top management; board of directors; transparency; disclosure; stakeholders